Shrine of Harsha Bhairon - Temples of India Project Team (Jio Institute, 2024)
Close to the Harshnath Temple complex is the Bhairon shrine, featuring a semi-iconic rock locally known as the Harsha Bhairon. He is believed to be a manifestation of the folk hero, Harsha, who decided to settle on the hill to worship Shiva and was blessed by the latter to be worshipped at the hill as Bhairon. Several 10th-century sculptures are fixed on the walls of this complex. Today, the Bhairon shrine serves as the epicenter of pilgrimage to Harsha Hill, considered to be the family deity of several local castes.